Об увеличении производительности дробеструйной камеры всасывающего типа - Воронин, С. Е.; Долгополов, В. Г.; Костенко, И. В.; Курцев, С. Н.; Скрипкин, Н. Р.; Федянин, А. В. (НТУ "ХПИ", 2007)
In the article calculation of feed of abrasive material for the suctiontype shot blasting chamber is made and scheme of its modernization is suggested.
Keywords: абразив; очистка поверхности